Tourism industry-driven changes in land use and ecological risk assessment at Jiuzhaigou UNESCO World Heritage Site. Issue 2 (3rd July 2018) - Yang, Xi; Wang, Juan; Sun, Xiaoqian; Zhang, Hengjin; Li, Ningxin; Liu, Jun
ABSTRACT: Using high-resolution satellite images of 2005 and 2015, we establishes a land use dataset for the Jiuzhaigou UNESCO World Heritage Site. It adopts ecosystem service value and landscape pattern indices to assess the effect of tourism development on ecological risk. The results find that from 2005 to 2015, tourism development has driven steady growth in construction land and transportation land. The ecosystem service value has declined sharply, while the overall ecological risk has increased. Areas closer to roads exhibit greater ecological risk, and different villages exhibit relatively large variations. The distribution of high-ecological risk zones progresses from dispersion to concentration.